Rainbow - Bauer, Marion Dane (Ready-to-read. Star reader!, 2016)
"What is that colorful arc in the sky? It is a rainbow. Rainbows are always pretty to look at, but where do they come from? The answer is at your fingertips. Just open this book and read about the wonders of rainbows ..."--